Immune responses to the adjuvanted recombinant zoster vaccine in immunocompromised adults: a comprehensive overview - Alemnew F. Dagnew; Peter Vink; Mamadou Drame; David O. Willer; Bruno Salaun; Anne E. Schuind (Taylor & Francis Group, 2021)
Immunocompromised (IC) persons are at increased risk for herpes zoster (HZ) and its complications, mainly due to impairment of cell-mediated immunity (CMI). The adjuvanted recombinant zoster vaccine (RZV) demonstrated efficacy against HZ in autologous hematopoietic stem cell transplant (auto-HSCT) recipients and hematologic malignancy (HM) patients. We review immune responses to RZV in 5 adult IC populations, 4 of which were receiving multiple, concomitant immunosuppressive medications: auto-HSCT and renal transplant recipients, HM and solid tumor patients, and human immunodeficiency virus-infected adults. Although administered in most cases when immunosuppression was near its maximum, including concomitantly with chemotherapy cycles, RZV induced robust and persistent humoral and, more importantly, CMI responses in all 5 IC populations. Based on the overall clinical data generated in older adults and IC individuals, RZV is expected to provide benefit in a broad adult population at risk for HZ.